PENETRATION TESTING DALAM FORENSIK DIGITAL PADA JARINGAN FAKULTAS TEKNIK UNIVERSITAS IBN KHALDUN BOGOR DENGAN PING OF DEATH - Quroturohman, Denis (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2021)
Network forensics is a computer security investigation to find sources of the attack s on the network by examining data log evidence, identifying, analyzing, and reconstructing the incidents. Types of attack s againist a computer or server on the network by spending resources that are owned by the computer until computer is not able to function properly, thus indirectly preventing other users to obtain access to network services that were attack ed is Distributed Denial of Service attack (DDoS). Network Forensics Research conducted in Research Laboratory of Information Engineering Master of Ahmad Dahlan University Yogyak arta. Detection of attacks carried out by Winbox RouterOS v3,6 where the software shows resources, attack er (IP Address), data pack ets, and when attack doing. Simulated attack s carried out by LOIC software to determine performance of safety system in computer network . To anticipate DDoS attack s,then developed a computer network security system.